Roland Barthes' Semiotic Analysis of the Representation of Family Communication in the Animated Film Coco (2017) - Lia Zuraida Surbakti; Muhammad Husni Ritonga (Journal of Social and Policy Issues, 2026)
This study aims to analyze the construction and interpretation of family communication in the animated film Coco (2017) using Roland Barthes's semiotic approach. The research focuses on how visual and narrative elements represent communication patterns within a family context, particularly through symbols such as the guitar, the ofrenda, ancestral photographs, and dialogues between characters. This study employs a qualitative method with media text analysis. Data were collected through observation and documentation of selected scenes, then analyzed using Barthes's three levels of meaning: denotation, connotation, and myth. This approach allows for a deeper understanding of how meanings are produced and culturally embedded within the film. The results show that at the denotative level, family communication is portrayed through everyday interactions and conflicts between characters. At the connotative level, these interactions reflect emotional bonds, authority structures, and the tension between individual desires and family expectations. At the myth level, the film reinforces cultural ideologies that prioritize family unity, respect for ancestors, and obedience to familial authority. In conclusion, Coco constructs family communication as a value-laden process shaped by cultural beliefs and intergenerational relationships, emphasizing harmony, collective identity, and the preservation of family traditions.